Interleukin-5 in the Pathophysiology of Severe Asthma - Pelaia, Corrado; Paoletti, Giovanni; Puggioni, Francesca; Racca, Francesca; Pelaia, Girolamo; Canonica, Giorgio Walter; Heffler, Enrico (Frontiers in Physiology, 2019)
Interleukin-5 (IL-5) exerts a central pathogenic role in differentiation, recruitment, survival and degranulation of eosinophils. Indeed, during the last years significant advances have been made in our understanding of the cellular and molecular mechanisms underlying the powerful actions of IL-5 finalized to the induction, maintenance and amplification of eosinophilic inflammation. Therefore, IL-5 is a suitable target for add-on biological therapies based on either IL-5 inhibition (mepolizumab, reslizumab) or blockade of its receptor (benralizumab). These modern treatments can result to be definitely beneficial for patients with severe type 2 (T2)-high eosinophilic asthma, refractory to conventional anti-inflammatory drugs such as inhaled and even systemic corticosteroids.